Familial adenomatous polyposis patients without an identified APC germline mutation have a severe phenotype. Issue 2 (14th January 2004) - Bisgaard, M L; Ripa, R; Knudsen, A L; Bülow, S
Abstract : Background: Development of more than 100 colorectal adenomas is diagnostic of the dominantly inherited autosomal disease familial adenomatous polyposis (FAP). Germline mutations can be identified in the adenomatous polyposis coli ( APC ) gene in approximately 80% of patients. The APC protein comprises several regions and domains for interaction with other proteins, and specific clinical manifestations are associated with the mutation assignment to one of these regions or domains. Aims: The phenotype in patients without an identified causative APC mutation was compared with the phenotype in patients with a known APC mutation and with the phenotypes characteristic of patients with mutations in specific APC regions and domains. Patients: Data on 121 FAP probands and 149 call up patients from 70 different families were extracted from the Danish Polyposis register. Methods: Differences in 16 clinical manifestations were analysed according to the patient's mutational status. Two sided independent t sample test, two sided χ 2 test, and odds ratios were calculated. Results: Patients without identified APC mutations had a unique and severe phenotype, which was roughly described as: young age at diagnosis and subsequent death in spite of development of few colorectal adenomas; low risk of involvement of the upper gastrointestinal tract, as reflected by a low mean Spigelman stage, and a low risk of fundic gland polyposis. Finally, they had significantly fewer affected family members, although they do not themselves more often represent an isolated case. Conclusions: The severe phenotype should be considered when counselling FAP families in which attenuated FAP is excluded and in which a causative APC mutation has not been identified.